Pengaruh Model Pembelajaran Kooperatif Tipe STAD (Student Team Achievement Division) dan Kompetensi Guru terhadap Kemampuan Berpikir Kritis pada Mata Pelajaran Akidah Akhlak di Madrasah Aliyah Darul Ulum Waru Sidoarjo - Isnaini, Ade Nur; Rodhiyah, Hj Siti Kholidatur; Al-Chumairoh, Nailul Ulah (YASIN, 2025)
The STAD type cooperative learning model is a learning model where students learn and work in small groups consisting of 4-6 students heterogeneously. The formation of heterogeneous groups means that diversity in gender, religious and socio-economic backgrounds, as well as academic abilities are not taken into account in group formation. This model can make students active, creative and think critically. This research aims to ; 1) Analyze the application of the STAD Type Cooperative Learning Model to improve students' critical thinking skills in Akidah Akhlak learning in MA. Darul Ulum Waru Sidoarjo. 2) Analyze the influence of teacher competence on improving students' critical thinking skills in Akidah Akhlak learning at MA. Darul Ulum Waru Sidoarjo. 3) Analyze the effect of implementing the STAD Type Cooperative Learning Model on students' critical thinking abilities in learning Akidah Akhlak in MA. Darul Ulum Waru Sidoarjo. This research uses a quantitative approach with an explanatory type of approach which is used to test a relationship between variables to find out whether a variable is influenced by other variables or not. The population in this study was class XI MA. Darul Ulum Waru Sidoarjo has a total of 406 students, and for the sample used 50 students of class testing. The results of the research show that there is an influence on the STAD type cooperative learning model (X1) and Teacher Competency (X2) on Critical Thinking Ability with an R square value of 0.457, which means that as much as 45.7% of Critical Thinking Ability is influenced by the STAD type cooperative model ( X1) and Teacher Competency (X2), while 54.3% was influenced by factors outside the research.